L’Istituto di Chimica dell’Università di Roma sotto la direzione di Nicola Parravano - Calascibetta, Franco (Chimica nella Scuola, 2024)
Nicola Parravano was one of the main protagonists of the Italian chemical community in the years between the two world wars. In that period, he was, among his many offices, the Director of the Chemical Institute of the Royal University of Rome. In this article the history of this institution is reconstructed and the personalities who worked in it are recalled, to better highlight the ideas and choices that inspired Parravano’s scientific and political action.